2019
DOI: 10.1080/02670844.2018.1433270
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and mechanical characterisation of electroplated nickel matrix composite coatings

Abstract: Metal matrix composite coatings reinforced with hard ceramic particles are attracting growing interest due to their promising mechanical properties. In the present work, a thick nickel coating, containing micrometric Silicon Carbide (SiC) particles, was electro-deposited on a steel substrate from a suspension of SiC in a Watts-type Ni-plating bath. The texture and microstructure of the coating were examined using electron backscatter diffraction combined with energy-dispersive spectroscopy for phase differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Beyond the realm of the models proposed by Yan et al, Cao et al, and Kashani et al, Constantinides et al argued in favor of using an indentation depth limit of 10% of the particle size [35]. Though Mercier et al appear to have had success applying the 10% rule identified by Constantinides et al in [36], the validity of Constantinides et al's approach suffers from the same short-comings associated with the models from Cao et al and the limit proposed by Kashani et al As will be subsequently shown, the alternatives to Yan et al's model are beset by regularly overestimating the upper bound of the particle-dominated indentation depth regimes, especially when the modulus of elasticity needs to be measured.…”
Section: Alternatives To the Yan Et Al Modelmentioning
confidence: 99%
“…Beyond the realm of the models proposed by Yan et al, Cao et al, and Kashani et al, Constantinides et al argued in favor of using an indentation depth limit of 10% of the particle size [35]. Though Mercier et al appear to have had success applying the 10% rule identified by Constantinides et al in [36], the validity of Constantinides et al's approach suffers from the same short-comings associated with the models from Cao et al and the limit proposed by Kashani et al As will be subsequently shown, the alternatives to Yan et al's model are beset by regularly overestimating the upper bound of the particle-dominated indentation depth regimes, especially when the modulus of elasticity needs to be measured.…”
Section: Alternatives To the Yan Et Al Modelmentioning
confidence: 99%
“…For stiff materials, the widely used method is the Oliver and Pharr model . Several publications prove the capability and sensitivity of the instrumented nanoindentation tests for the determination of the intrinsic mechanical parameters for single materials (Lin et al, 2009), thin films deposited on substrate (Li & Vlassak, 2009) (Bae et al, 2004) (Liu et al, 2015) and composite materials (Ho & Marcolongo, 2005;Ureña et al, 2005;Kossman et al, 2019;Mercier et al, 2019).…”
Section: Nanoindentation Testsmentioning
confidence: 94%
“…The inclusion of small particles as the second step increases the surface hardness, corrosion resistance, wear resistance, and rising temperature inertness of composite coatings [17]. These characteristics are primarily determined by each matrix phase of a composite coating, as well as the quantity and dispersion of co-deposited grains, which are controlled by some process factors including particle properties, electrolyte composition, and supplied current [18,19].…”
Section: Abstract a R T I C L E I N F O R M A T I O Nmentioning
confidence: 99%